2021 Fertilizer Weather Station Report - M. Sittel (Kansas Agricultural Experiment Station Research Reports, 2022)
This report includes the annual summary of precipitation and temperatures from 2021 at the research locations represented in the 2022 fertilizer report.
Keywords: Kansas State experiment field; 2021 growing season weather; Kansas weather; fertilizer research